The association between composite dietary antioxidant index and diabetic retinopathy in type 2 diabetic patients: evidence from the NHANES - Liu, Shasha; Zhu, Zhanfang; Yu, Kai; Zhang, Wei; Pu, Jie; Lv, Ying; Tang, Zhiguo; Liu, Fuqiang; Sun, Yongqiang (Frontiers in Nutrition, 2024)
Background Although diabetic retinopathy (DR) is closely related to dietary patterns and oxidative stress, there is little research on the relationship between the compound dietary antioxidant index (CDAI) and DR. This study aims to fill this gap by analyzing data from the National Health and Nutrition Examination Survey (NHANES) to explore the association between CDAI and DR in patients with type 2 diabetes, in order to provide a basis for dietary guidance to prevent DR. Methods Data for this study was obtained from NHANES conducted between 1999 and 2020. Information regarding dietary intake was collected through 24 h dietary recall interviews. Multivariate logistic regression analyses and restricted cubic splines (RCS) were employed to explore the association between CDAI and DR. Furthermore, subgroup analyses were conducted to further examine the relationship. Results In this study, a total of 2,158 participants were included, with a mean age of 58.87 years. After adjusting for all potential confounding factors, multivariate logistic regression analyses consistently demonstrated a negative correlation between CDAI and DR (OR = 0.94, 95%CI: 0.90–0.98, p = 0.007). Specifically, individuals in the highest quartile of CDAI had a significantly reduced risk of DR compared to those in the lowest quartile (OR = 0.51, 95%CI: 0.34–0.75, p < 0.001). The RCS analyses further confirmed the linear negative correlation between CDAI and DR (non-linear p = 0.101). Additionally, subgroup analyses provided further evidence for the robustness of this association across different subpopulations. Conclusion Our study highlights the linear negative correlation between CDAI and DR in type 2 diabetic patients. Further prospective studies are still needed in the future to confirm the role of CDAI in the risk of developing DR.